2010
DOI: 10.5336/medsci.2008-9832
|View full text |Cite
|
Sign up to set email alerts
|

Mobbing Behaviors Encountered by Health Science Faculties Staff and Their Responses to Them

Abstract: Ö ÖZ ZE ET T A Am ma aç ç: : Iş yerinde psikolojik şiddet, bir ya da birkaç kişinin tek bir kişiye sistemli olarak yönelttik-leri, etik dışı iletişim ile düşmanca davranışlarda bulunulması olarak tanımlanmaktadır. Bu çalışma üniver-sitelerde çalışan akademik personelin iş yerinde karşılaştığı psikolojik şiddet davranışlarını ve bu davranışların çalışanlar üzerindeki etkilerini belirlemek amacıyla kesitsel ve tanımlayıcı olarak gerçek-leştirilmiştir. G Ge er re eç ç v ve e Y Yö ön nt te em ml le er r: : Web ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 7 publications
4
13
0
Order By: Relevance
“…On the other hand one out of seven academicians (16.6%) stated that they were directly exposed to psychological violence behaviors. Some recent studies conducted in universities [17,19,22], in accordance with our results, revealed out that the frequency of directly mobbing may reach to 17-29% in academic personnel. In addition, the frequency of verbal mobbing experienced by academicians in our study was similar to that of another study [20] but it was lower compared to other two studies [17,25].These studies reported that the rate of verbal mobbing behaviors was between 82-90 %.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…On the other hand one out of seven academicians (16.6%) stated that they were directly exposed to psychological violence behaviors. Some recent studies conducted in universities [17,19,22], in accordance with our results, revealed out that the frequency of directly mobbing may reach to 17-29% in academic personnel. In addition, the frequency of verbal mobbing experienced by academicians in our study was similar to that of another study [20] but it was lower compared to other two studies [17,25].These studies reported that the rate of verbal mobbing behaviors was between 82-90 %.…”
Section: Discussionsupporting
confidence: 79%
“…Some recent studies conducted in universities [17,19,22], in accordance with our results, revealed out that the frequency of directly mobbing may reach to 17-29% in academic personnel. In addition, the frequency of verbal mobbing experienced by academicians in our study was similar to that of another study [20] but it was lower compared to other two studies [17,25].These studies reported that the rate of verbal mobbing behaviors was between 82-90 %. Differences in the rate of mobbing in these studies may be a result of using different mobbing definitions, scales [21,25] settings and participants(academic staff, only academic nurses, only physicians [14] and differences perceptions of workplace violence [1,26,27].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations